3-Way Security for Packet Transmission (International Journal of Engineering and Computer Science, 2014)
Encoding is the process of converting data into a format required for a number of information. Encoding involves the use of a code to change original data into a form that can be used by an external process. Interleaving is a process or methodology to make a system more efficient, fast and reliable by arranging data in a non-contiguous manner. Interleaving divides memory into small chunks. It is used as a high-level technique to solve memory issues for motherboards and chips. By increasing bandwidth so data can access chunks of memory, the overall performance of the processor and system increases. Modulation is the addition of information (or the signal) to an electronic or optical signal carrier. Modulation can be applied to direct current (mainly by turning it on and off), to alternating current, and to optical signals     to inimize the impact of an unintentional disruption, it is important to identify its presence. Jamming makes itself known at the physical layer of the network, more commonly known as the MAC (Media Access Control) layer. The increased noise floor results in a faltered noise-to-signal ratio, which will be indicated at the client. It may also be measurable from the access point where network management features should able to effectively report noise floor levels that exceed a predetermined threshold. From there the access points must be dynamically reconfigured to transmit channel in reaction to the disruption as identified by changes at the physical layer.